OPTIMIZATION DESIGN AND NUMERICAL ANALYSIS OF WIND ROTOR IN THE SAVONIUS WIND TURBINE - CHEN Wei; HUNAG WenQuan; LI KaiShi (Jixie qiangdu)
In order to improve the rotor power coefficient of Savonius wind turbine,the turbine of the wind energy utilization rate as the optimization goal,a wind rotor diameter、air gap and height as variables,and the Baez limit and related experimental results as constraint conditions,established the structure parameter optimization model of wind rotor,and use Matlab to solve the optimal structure size. In order to make the wind energy utilization rate higher,the wind turbine structure form is improved,and the 3D modeling is established,and the Workbench ANSYS is used to carry out the fluid structure coupling analysis,and the reliability of the optimized and improved wind rotor structure is verified.